Scar revision - Mohit Sharma; Abhijeet Wakure (Indian Journal of Plastic Surgery)
Most surgical patients end up with a scar and most of these would want at least some improvement in the appearance of the scar. Using sound techniques for wound closure surgeons can, to a certain extent, prevent suboptimal scars. This article reviews the principles of prevention and treatment of suboptimal scars. Surgical techniques of scar revision, i.e., Z plasty, W plasty, and geometrical broken line closure are described. Post-operative care and other adjuvant therapies of scars are described. A short description of dermabrasion and lasers for management of scars is given. It is hoped that this review helps the surgeon to formulate a comprehensive plan for management of scars of these patients.